Fundamental of Entrepreneurship ENT300 : Arrow Sport Fitness / Muhamad Nazrin Abd. Halim ... [et al.] - Abd. Halim, Muhamad Nazrin; Wan Sukoran, Wan Amirrul Hasyim; Mohamad, Nor Farizul Hakim; Hassim @ Hashim, Sulaimie; Wan Abu Bakar, Wan Hazmi (2013)
Arrow Sport Fitness is a partnership company aimed to provide the customers with gymnasium services. There are five members of this company partnership which consist of the General Manager, Administration Manager, Operation Manager, Marketing Manager, and Financial Manager. The major objective of our company is to provide customers in Stutong area with fitness and health centre that can fulfil their needs and demands. Arrow Sport Fitness is design with its different services that have not yet been offered in any fitness centre in Kuching or even in Samarahan area. What makes our business so unique and different is that we offer a separate gymnasium for the men and women. For women, they will use our cardio area because it is suitable for them to do workout. With this new type of services we will be able to compete and attract more customers especially among the women to our fitness centre.